2021
DOI: 10.1111/bph.15658
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam attenuates the effects of cocaine on locomotion, 50‐kHz ultrasonic vocalizations and phasic dopamine in the nucleus accumbens of rats

Abstract: Background and Purpose: Currently, there is no effective drug to treat cocaine-use disorder, which affects millions of people worldwide. Benzodiazepines are potential therapeutic candidates, as microdialysis and voltammetry studies have shown that they can decrease dopamine concentrations in the nucleus accumbens of rodents and block the increase in dopamine levels and appetitive 50-kHz ultrasonic vocalizations (USVs) induced by amphetamine in rats.Experimental Approach: Here, we tested whether administration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Recent research showed that CBD can be effective in reducing the reward and reinforcement effects of addictive drugs (Galaj et al, 2020 ). Among the drugs that affected the three genes, diazepam and melatonin might be useful therapeutic agents for reducing cocaine abuse (Takahashi et al, 2017 ; Barbosa-Méndez et al, 2021 ; Sanchez et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research showed that CBD can be effective in reducing the reward and reinforcement effects of addictive drugs (Galaj et al, 2020 ). Among the drugs that affected the three genes, diazepam and melatonin might be useful therapeutic agents for reducing cocaine abuse (Takahashi et al, 2017 ; Barbosa-Méndez et al, 2021 ; Sanchez et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The indole group of anlotinib has been found to effectively inhibit Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) and Vascular Endothelial Growth Factor Receptor 3 (VEGFR3), thereby preventing the formation of tumor vasculature and lymphatic vasculature and suppressing tumor metastasis [18,19]. Relevant clinical data [20,21] has indicated that the objective response rate and disease control rate of patients with advanced lung adenocarcinoma resistant to previous treatment could reach more than 40% and 80%, respectively, when treated with anlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the demand for the treatment of cocaine use disorder, the regulatory agencies for drug safety have not approved any pharmacological treatment for cocaine addiction (Sanchez et al, 2022). Most medications used were developed for other medical conditions.…”
Section: Linked Articlesmentioning
confidence: 99%
“…Substance use disorders are conditions where effective pharmacotherapy is limited, risky or not available, and hence another area where effective pharmacotherapeutics are needed. There is evidence that intranasal oxytocin administration may be of benefit due to its anti-craving properties (Houghton et al, 2021published Despite the demand for the treatment of cocaine use disorder, the regulatory agencies for drug safety have not approved any pharmacological treatment for cocaine addiction (Sanchez et al, 2022).…”
mentioning
confidence: 99%